ANALISIS KEKUATAN SAMBUNGAN KAYU MENGGUNAKAN EPOXY DGEBA PADA GELADAK ATAP KAPAL KAYU TRADISIONAL - Rosdiyantoro Syarif S. J.; Imah Luluk K (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
Wood remains a widely used construction material in the shipbuilding industry. However, the limited availability of high-quality wood has led to a decline in material performance, particularly due to the reliance on younger trees with lower mechanical properties. To address this challenge, proper joining techniques are required, and the quality of such joints must be carefully evaluated. The aim of this study is to analyze the strength of wood joints using DGEBA epoxy on the deck roof of wooden ships. Two connection models were investigated: the wood laminate model and the double sawn model, both bonded with DGEBA epoxy adhesive. The strength of the specimens was evaluated through bending and tensile tests. The results showed that the laminated joints achieved bending and tensile strengths of 41.86 MPa and 10.57 MPa, respectively, while the double sawn joints exhibited values of 54.68 MPa in bending and 1.33 MPa in tension.